The purification of a cysteine-dependent NAD+ glycohydrolase activity from bovine erythrocytes and evidence that it exhibits a novel ADP-ribosyltransferase activity. - Saxty, B A (1995)
An NAD+:cysteine ADP-ribosyltransferase activity was purified from bovine erythrocytes on the assumption that, like pertussis toxin, the enzyme would exhibit a cysteine-dependent NAD+ glycohydrolase activity. A three-step purification procedure was developed involving (1) precipitation with 40% (NH4)2SO4, (2) binding to a cysteine-Sepharose affinity column, and (3) binding to an NAD+ affinity column. PAGE showed a single band of M(r) 45,000. The enzyme had been purified 47,000-fold and had a specific activity of 1900 nmol nicotinamide released/min per mg. A study of the kinetic properties of this enzyme showed saturation kinetics for cysteine (Km = 4.0 mM). The ability of this enzyme to ADP-ribosylate protein was investigated using re-sealed inverted bovine erythrocyte ghosts. Incubation of the purified enzyme with erythrocyte ghosts and [adenylate-32P]NAD+ led to the enhanced dose-dependent labelling of several proteins, a doublet of high M(r) and proteins of M(r) 60,000, 55,000 and 29,000, identified by autoradiography of separated proteins on SDS/PAGE. The enzyme-catalysed labelling of the major component at M(r) 55,000 was blocked by pre-treatment of the erythrocyte ghosts with N-ethymaleimide, a sulphydryl alkylating agent, and the label was released by mercuric ion, but not by hydroxylamine. These experiments suggested that a cysteine residue on the target protein had been mono-ADP-ribosylated. This supposition was further supported by identification of the mercf1p4ion-released radiolabelled product as ADP-ribose by HPLC, and the observation that free ADP-ribose was unable to modify the membrane target protein directly.